2000
DOI: 10.1007/s004310000587
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lung disease of prematurity. The role of intra-uterine infection

Abstract: Intra-uterine infection is not only a common cause of preterm onset of labour but also a trigger to lung injury which significantly increases the risk of development of long-term respiratory disease in the newborn infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 38 publications
1
46
0
2
Order By: Relevance
“…However, recent research has focused on the roles of perinatal infection and the inflammatory response as critical factors influencing chronic lung injury (7,16). Particular attention has been paid to the role of Ureaplasma species, fastidious bacteria found in the lower genital tracts of 40 to 80% of asymptomatic women (4).…”
mentioning
confidence: 99%
“…However, recent research has focused on the roles of perinatal infection and the inflammatory response as critical factors influencing chronic lung injury (7,16). Particular attention has been paid to the role of Ureaplasma species, fastidious bacteria found in the lower genital tracts of 40 to 80% of asymptomatic women (4).…”
mentioning
confidence: 99%
“…The multifactorial etiology of BPD of the newborn has been reported over the last three decades (Bancalari et al, 2003;Jobe and Bancalari, 2001;Kinsella et al, 2006;Speer, 2003;Speer, 2006) With the increased survival of a greater number of more immature infants, the contribution of antenatal infection to BPD has been argued (Jobe, 2003;Lyon, 2000;Miralles et al, 2002). Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that development of BPD (CLD) is related to pulmonary immaturity, oxidant injury due to high levels of inspired oxygen, and volutrauma associated with mechanical ventilation. However, recent research has focused on the roles of perinatal infection and the inflammatory response as critical factors influencing chronic lung injury (De Dooy et al, 2001;Lyon, 2000). Particular attention has been given to the role of Ureaplasma species, found in the lower genital tracts of 40 to 80% of asymptomatic women (Cassell et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to causing the release of proinflammatory mediators, lung infection, either congenital or nosocomial, may result in the necessity for ventilatory support, which deteriorates pulmonary damage even further. 1,[14][15][16][17] Patent Ductus Arteriosus (PDA): PDA causes an increase in pulmonary blood flow and interstitial edema, reducing lung compliance and increasing airway resistance. This may result in a more aggressive and prolonged ventilatory strategy, elevating the risk for the development of BPD.…”
Section: Factors Associated With Lung Injurymentioning
confidence: 99%